Analysis of Priority Vaccine-Preventable Diseases Using the PAHO-Adapted Hanlon Method in Bogor City in 2024 - Ketaren, Sonia Annisa Br; Wahyono, Tri Yunis Miko; Kusnadi, Bai (Jurnal Epidemiologi Kesehatan Indonesia, 2026)
Vaccine-preventable diseases (VPDs) remain a major public health challenge despite substantial progress in immunization programs. In Indonesia, routine immunization coverage has shown a post-pandemic recovery trend; however, disparities in access to health services and surveillance quality persist across regions. This study aimed to determine priority VPD problems in Bogor City and identify factors contributing to the highest-ranked disease. A mixed-methods study was conducted in Bogor City from October 2024 to January 2025. Quantitative prioritization was performed using the Pan American Health Organization (PAHO)-adapted Hanlon method across eight VPDs. Qualitative data were collected through in-depth interviews with key informants and analyzed thematically. Findings were presented using an Ishikawa diagram. Hepatitis B was identified as the highest-priority VPD (10.91), followed by cervical cancer (9.21) and measles (6.44). Factors contributing to the persistence of hepatitis B included limited public awareness, incomplete surveillance and contact tracing, suboptimal intersectoral coordination, inadequate monitoring and reporting systems, and insufficient program support. The PAHO-adapted Hanlon method provides a structured framework for evidence-based priority setting. Strengthening hepatitis B control requires improved health literacy, strengthened surveillance systems, enhanced intersectoral collaboration, and optimized monitoring and evaluation. Keywords: Vaccine-preventable diseases, Health priority setting, Hepatitis B, Hanlon method, Public health surveillance